Proof in the Pudding: The Value of a Rights Based Approach to Understanding the Covert Administration of Psychotropic Medication to Adult Inpatients Determined to Be Decisionally-Incapable in Ontario's Psychiatric Settings. Issue 2 (June 2017) - Sheldon, C. Tess
This paper explores a grey area of psychiatric practice and, as with other challenging practices, the law is called upon to navigate conflicting legal issues. In particular, this paper explores the covert administration of medication: the concealment of medication in food or drink so that it will be consumed undetected. Rights-based approaches support nuanced understanding of the practices. Few policies, protocols or guidelines govern the practice in Ontario's psychiatric settings. While covert medication is understood to have "something to do" with rights, there is confusion about how those rights play out on the ground. Institutional silences underlie and reinforce the practice. Most pressing, the covert administration of medication warrants an overt discussion, including of its impact on the rights-experience of persons in psychiatric settings.